Alliance Leadership - Moxley, Virginia (Institute for Academic Alliances, 2009)
Leading an alliance is inherently striving for balance between alliance and individual institution interests. In this paper, Dr. Virginia Moxley details several strategies for ensuring that alliance and institutional interests are in accord. When these interests align, a successful alliance is possible.
Keywords: Institute for Academic Alliances; Consortium Administration; Teamwork; Leadership; Higher education administration